Learning Management Process and Media and Information Literacy in Thailand - Tukphimai, Sangwan (Technium Social Sciences Journal, 2022)
Moving forward to the convergence of media and information era has much affected Thai youths and societies. Teaching to build media and information literacy skills to learners has been accepted as a basis of transferring bodies of knowledge to youths in order to furnish learners with wisdom arms for further media and information selection. Learning process to build media and information literacy skills consists of 7 phases i.e. 1) elicitation phase- to encourage learners in expressing their prior knowledge, 2) engagement phase- to guide learners to interesting learning contents from their own interests or from group discussion, 3) exploration phase- after learners understand interested questions or issues to be studied, a plan with guidelines, exploration, hypothesis, specifying alternatives, and implementation will be set for further data collection, 4) explanation phase- after data are collected, they will be analyzed, interpreted, concluded, and presented which can build knowledge and raise learning to learners, 5) elaboration phase- the newly built knowledge is linked with prior knowledge or concepts, or the newly built model or conclusion can be applied to explain other situations or events, 6) evaluation phase- learning is evaluated by various processes to find what are learnt by learners, and quantity of learning which will assist learners to further application of the gained knowledge, 7) extension phase- providing opportunities to learners to apply the gained knowledge in their daily living. Teachers play an important role in encouraging learners to build further new knowledge from the gained one and learners, then, can transfer learning to others as well.